2006
DOI: 10.1186/1471-2458-6-99
|View full text |Cite
|
Sign up to set email alerts
|

Local public health workers' perceptions toward responding to an influenza pandemic

Abstract: Background: Current national preparedness plans require local health departments to play an integral role in responding to an influenza pandemic, a major public health threat that the World Health Organization has described as "inevitable and possibly imminent". To understand local public health workers' perceptions toward pandemic influenza response, we surveyed 308 employees at three health departments in Maryland from March -July 2005, on factors that may influence their ability and willingness to report to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
292
6
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(335 citation statements)
references
References 6 publications
28
292
6
9
Order By: Relevance
“…In the United States of America (USA), between April 2009 and March 2010, it was responsible for an estimated 192,000 to 398,000 hospitalizations and 8,720 to 18,050 deaths (CDC, 2010). The effective management of pandemic influenza continues to constitute a major concern throughout the public health community (Balicer et al, 2006;Ferguson et al, 2006). A key issue facing the public health community includes the development of strategies for reducing the spread and effects of pandemic influenza.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States of America (USA), between April 2009 and March 2010, it was responsible for an estimated 192,000 to 398,000 hospitalizations and 8,720 to 18,050 deaths (CDC, 2010). The effective management of pandemic influenza continues to constitute a major concern throughout the public health community (Balicer et al, 2006;Ferguson et al, 2006). A key issue facing the public health community includes the development of strategies for reducing the spread and effects of pandemic influenza.…”
Section: Introductionmentioning
confidence: 99%
“…environmental disasters, mass casualty incidents) 11) . In another study on public health workers, Balicer et al found that almost half of HCWs were unlikely to report to duty during an influenza pandemic 12) . In a study by Ruderman et al after the SARS outbreak, healthcare professionals questioned their choice of career and decided to leave their profession and pursue new ventures, showing an unwillingness or inability to care for patients in the face of risk 13) .…”
Section: Concernsmentioning
confidence: 99%
“…5 However, a study in 2005 found that other factors, including one's ''perceived self-importance in an organization,'' contributed to willingness to respond. 6 This finding has influenced recent research using the Extended Parallel Process Model (EPPM) to understand willingness to respond in local public health workers, emergency medical technicians, and hospital workers. [7][8][9][10] First introduced by Witte in 1992, the EPPM interprets an effective message as one that conveys 2 equally important parts: threat and efficacy.…”
mentioning
confidence: 99%